PENGARUH PROBLEM-BASED LEARNING (PBL) BERSTRATEGI â€œMURDERâ€ TERHADAP KEMAMPUAN PENALARAN MATEMATIS SISWA - Fatimah, Lutfiah; Maulana, M.; Isrok'atun, I. (Jurnal Pena Ilmiah, 2017)
The use of Problem-Based Learning (PBL) with â€œMURDERâ€ strategy in primary schools is still rare in Indonesia. Problem-Based Learning (PBL) strategy "MURDER" is one of the main innovative and appropriate collaboration between the approaches and strategies to give effect to the students' mathematical reasoning skills. Studentsâ€™ mathematical reasoning skills is one of the main skill that students need to have in the problem solving process. This study was conducted to determine the effect of Problem-Based Learning (PBL) strategy "MURDER" of mathematical reasoning skills of students. The method used is a quasi experiment with nonequivalent control group design. The population in this research is the entire class of grade V elementary school in Kuningan regency, with the sample chosen SDN 4 Jalaksana as an experimental class and SDN Padamenak as the control class.